Generation and Characterization of Osterix-Cherry Reporter Mice - Strecker, Sara (2012)
Osterix is a zinc finger containing transcription factor, which functions as a key regulator of osteoblast differentiation. To better understand the temporal and spatial expression of Osterix during embryonic development and in the adult skeleton, we generated Osterix-Cherry reporter mice. Bacterial recombination techniques were employed to engineer a transgenic construct, which consisted of a ~39kb DNA fragment encompassing the Osterix/Sp7 gene, but excluding adjacent gene sequences. Osterix reporter expression was characterized at embryonic, neonatal, and adult ages both by itself and in the context of a cross with Bone Sialoprotein (BSP)-Topaz reporter mice. Relative to Osterix, BSP is a more mature marker of osteoblast differentiation. In agreement with osteoblast lineage maturation, Osterix reporter expression preceded BSP reporter expression during embryonic development and spatially appeared in a much broader cell population. Strong Osterix reporter expression was observed in mature osteoblasts and osteocytes. However, weaker Osterix-Cherry positive cells were also observed in the bone marrow, possibly identifying an early osteoprogenitor cell population. Evaluation of Osterix reporter expression in male femur tissue sections from 10 days to 12 weeks of age revealed persistent expression in cells of the osteoblast lineage and a surprising increase in maturing chondrocytes of the growth plate. Also, Osterix reporter expression was transiently detected in the kidney after birth.